Application of the Maximum Principle to Minimizing Total Production Costs - Kiselev, V. V. (Journal of mathematical sciences (New York, N.Y.), 2023)
There are no common methods of the search for optimal solutions to problems of economic dynamics. Application of variational methods is possible for a quite narrow class of problems. In this paper, we discuss application of the Pontryagin maximum principle, which significantly expands the class of problems considered and allows one to obtain numerical solutions.